(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This article discusses pragmatics and stylistics which are one of the significant branches of linguistics. It studies the connections of pragmatics with stylistics. Furthermore, it finds out some essential aspects of the branches with examples in English and Uzbek